Mortality of Japanese Olympic athletes in 1964 Tokyo Olympic Games - Takeuchi, T.; Kitamura, Y.; Ishizuka, S.; Yamada, S.; Aono, H.; Kawahara, T.; Sobue, T. (BMJ Open Sport & Exercise Medicine, 2021)
Objectives To compare the mortality of Japanese athletes in the 1964 Tokyo Olympic Games with that of the Japanese population, and to elucidate factors associated with their mortality.